2019
DOI: 10.4103/jlp.jlp_106_19
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of Ki-67, p53, and CD10 in phyllodes tumor and their correlation with its histological grade

Abstract: CONTEXT: Phyllodes tumors (PTs) are the fibroepithelial neoplasms of the breast. Histologically, PTs are divided into three subgroups according to their clinicopathological behavior: benign, borderline, and malignant. It is at times difficult to ascertain the grade of PT on morphological criteria alone, especially borderline PT may be at times difficult to distinguish from its benign or malignant counterparts. AIMS: This study was undertaken to evaluate an immunohistochemical panel of Ki-67, p53, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…A variety of biomarkers such as Ki-67 and p53 protein expression have been proposed to help with subclassi cation of phyllodes tumors (13,14), and the expression of c-kit (CD117), phospho-histone3, MDM2, ERG, CD31, CD34 have been reported to be predictive of malignant behavior of PT (13,15,16). However, these ancillary studies have not been shown to be independent predictive and prognostic biomarkers (17).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of biomarkers such as Ki-67 and p53 protein expression have been proposed to help with subclassi cation of phyllodes tumors (13,14), and the expression of c-kit (CD117), phospho-histone3, MDM2, ERG, CD31, CD34 have been reported to be predictive of malignant behavior of PT (13,15,16). However, these ancillary studies have not been shown to be independent predictive and prognostic biomarkers (17).…”
Section: Introductionmentioning
confidence: 99%
“…This fact has been reported in a retrospective study which analyzed the link between the expression of three immunomarkers (Ki67, p53 and CD10) and the HP grade of the PTs. The expression of these markers was evaluated both in the stroma and in the epithelium [ 40 ]. There was a statistically significant difference of the immunomarkers’ expression in the stroma between the three types of PTs, but not in the epithelium.…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…Stromal Ki67 labeling index were at least double in malignant phyllodes compared with benign phyllodes. The immunohistochemical evaluation might play an important role in differentiation benign form malignant PTs, thus Ki67 and p53 could be prognostic biomarkers [ 40 , 41 ]. In only four of the revised cases, including our own, immunohistochemical examination was performed on the post-operative specimen and none on the core needle biopsies.…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…Additionally, CD10 expression in PT strongly correlates with tumor grade as per the WHO grading system. [14][15][16] Chen et al found that among malignant PT, 75% were positive for KIT% and 67% for SMA. 17 By comparison and similar to this study, in our cohort 75% of the PST were positive for KIT% and 75% were positive for SMA; 100% were positive for CD10.…”
Section: Discussionmentioning
confidence: 99%